If wishes were retail - Habershaw, Auston, 1979- (Tachyon Publications, 2025)
"In this hilarious debut fantasy cozy, a rebellious--but enterprising--young woman and an ancient--but clueless--genie set up shop at the local mall. Alex Delmore needs a miracle. She wants out of her dead-end suburban town, but her parents are broke and NYU seems like a distant dream. Good thing there's a genie in town--and he's hiring at the Wellspring Mall. It'd help if the Jinn-formerly-of-the-Ring-of-Khorad knew even one thing about 21st-century America. It'd help if he weren't at least as stubborn as Alex. It'd really help if her brother didn't sell her out to her conspiracy theory-loving, gnome-hating dad. When Alex and the genie set up their wishing kiosk, they face seemingly-endless setbacks. The mall is failing and management will not stop interfering on behalf of their big-box tenants. But when the wishing biz might start working, the biggest problem of all remains: People are really terrible at wishing." --Provided by Publisher